Academic Pathology Departments and Associated Children's Hospitals: An Overview of the Relationship - David N. Bailey MD (Elsevier, 2020)
A survey of academic pathology departments was conducted in order to evaluate the relationship with their associated children's hospitals. Forty percent (88) of US children's hospitals were associated with academic pathology departments. Sixty percent of pathology department respondents indicated that their children's hospital was part of their academic health system. As a reflection of this, the majority (54%) of all respondents reported that their children's hospitals were physically located within the academic health care system itself. Accordingly, a vast number (94%) of academic departments reported that they performed the clinical services for those children's hospitals that were part of their academic health system. For those associated children's hospitals that were not part of the academic health system, 70% of respondents reported that the academic pathology department provided at least some clinical services for them. The number of pathologists in the children's hospital pathology departments that were not part of the academic health system ranged from 1 to 5 (41%), 6 to 10 (18%), and >10 (41%), with one-third having salaried faculty appointments in the academic pathology department. The chief of pathology in those children's hospital departments was part of the academic department leadership team in half of the cases. Although 86% of respondents reported that pathology residents rotate through the associated children's hospital, in only 26% of instances did the children's hospital provide resident support for the academic pathology department. The perceived strengths and weaknesses of the relationship between academic pathology departments and associated children's hospitals are discussed.